The Resilient Manager Navigating the Challenges of Working Life - Furnham, Adrian. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Resilient people are happier, healthier, and more productive. Psychologist and business writer Adrian Furnham takes a sideways and entertaining look at the challenges of being a leader, demonstrating how resilience can be honed, developed, and used as a personal life raft to keep afloat in the face of adversity.